Capturing the ups and downs of accidents’ figures – the Portuguese case study - Leão, Celina Pinto (2019)
Nowadays, the need to obey the Portuguese legislation compels the employer to establish a safety management structure within the company that mirrors the legal-binding prevention general principles, patent in the legal framework for the Promotion of Occupational Safety and Health (OSH). Moreover, Safety and Health at Work Management System, also evokes the importance of Safety in the current occupational arena in Portugal, where Safety is also a strategic target for companies, not only for image issues but also for the proven benefits of certification. Given this, it would seem logical to assume that the data reporting the number of accidents’ occurrence would naturally diminish in the course of the years. What one observes, however, is that these numbers oscillate, presenting ups and downs throughout the last years. What has happened, then? This article proposes to look within those numbers, describe their behavior and critically analyze them.